Seaweeds from Neovolcanic rocky shores of Veracruz, Mexico - Landa-Cansigno, Cristina; Mateo-Cid, Luz Elena; Mendoza-González, Angela Catalina; Guerrero-Analco, José Antonio (Instituto de Ecología, A.C., 2019)
Background and Aims: The rocky shore environments of the state of Veracruz are unique sites in which the macroalgal richness has been poorly studied, mainly due to the absence of complete floristic lists and a follow-up of the changes in algal populations. Hence, the goal of this work was to contribute to the knowledge of algae of Veracruz rocky shore environments located in Playa Paraíso, Playa Villa Rica and Playa Muñecos, which are influenced by the foothills of the Neovolcanic Belt.Methods: Seaweeds were collected during rainy (September 2016) and dry seasons (May 2017) on selected rocky shores named “Playa Paraíso” (PP), “Playa Villa Rica” (PVR) and “Playa Muñecos” (PM). Samples were preserved in a seawater and formaldehyde (4%) solution. External and internal morphometric observations were carried out on the thalli, and the species were determined according to specialized taxonomic literature.Key results: A total of 45 species were identified, from which 18 were Chlorophyta, 16 Rhodophyta and 11 Ochrophyta. The most representative families found were Corallinaceae, Rhodomelaceae, Cladophoraceae and Dictyotaceae. The highest richness of species was observed in PP during the dry season. New records are reported for the localities, of which Centroceras gasparrinii, Gracilaria apiculata and G. flabelliformis are new records for the state of Veracruz.Conclusions: The algal flora of the Neovolcanic rocky coast of Veracruz is tropical and houses 31% of the regional algal flora of the state. The new records in each of the localities reflect a gap in the knowledge of the algal richness of this area. As a consequence, it is suggested to continue recording species occurrence in the area in order to integrate the corresponding floristic lists.